Vaginal cancer treated with curative radiotherapy with or without concomitant chemotherapy: oncologic outcomes and prognostic factors - Meixner, Eva; Arians, Nathalie; Bougatf, Nina; Hoeltgen, Line; König, Laila; Uzun-Lang, Kristin; Domschke, Christoph; Wallwiener, Markus; Lischalk, Jonathan W.; Kommoss, Felix; Debus, Jürgen; Hörner-Rieber, Juliane (Tumori journal, 2023)
Background:Vaginal cancer is a rare disease for which prospective randomized trials do not exist. We aimed to assess survival outcomes, patterns of recurrence, prognostic factors, and toxicity in the curative treatment using image-guided radiotherapy (RT).Methods:In this retrospective review, we identified 53 patients who were treated at a single center with external beam radiotherapy and brachytherapy with or without concomitant chemotherapy from 2000 to 2021.Results:With a median follow-up of 64.5 months, the Kaplan-Meier 2-, 5-, and 7-year overall survival (OS) was found to be 74.8%, 62.8%, and 58.9%, respectively. Local and distant control were 67.8%, 65.0%, and 65.0% and 74.4%, 62.6%, and 62.6% at 2, 5, and 7 years, respectively. In univariate Cox proportional hazards ratio analysis, OS was significantly correlated to FIGO stage (hazard ratio [HR] 1.78, p = 0.042), postoperative RT (HR 0.41, p = 0.044), and concomitant chemotherapy (HR 0.31, p = 0.009). Local control rates were superior when an equivalent dose in 2-Gy fractions (EQD2) of ?65 Gy was delivered (HR 0.216, p = 0.028) and with the use of concurrent chemotherapy (HR 0.248, p = 0.011). Not surprisingly, local control was inferior for patients with a higher TNM stage (HR 3.303, p = 0.027). Minimal toxicity was observed with no patients having documentation of high-grade toxicity (CTCAE grade 3+).Conclusion:In treatment of vaginal cancer, high-dose RT in combination with brachytherapy is well tolerated and results in effective local control rates, which significantly improve with an EQD2(α/?=10) ?65 Gy. Multivariate analyses revealed concomitant chemotherapy was a positive prognostic factor for overall and progression-free survival.
First published online November 1, 2021
Gesehen am 06.02.2023